Investigation of the decomposition and leaching dynamics of Salix, Populus and mixed leaves in the area of Lake Balaton and Kis-Balaton Wetland - Simon, Brigitta; Kucserka, Tamás; Anda, Angéla (Acta Agraria Debreceniensis, 2019)
In lakes and wetlands, leaf litter input from the coastal vegetation represents a major nutrient load and plays a basic structural and functional role in several ecosystems. In Hungary, at the banks of lakes and wetlands, Salix and Populus trees are the most common species. In an experiment in Lake Balaton and Kis-Balaton Wetland between 16 November 2017 to and 3 June 2018, the decomposition rates and leaching dynamics of Salix, Populus and mixed leaves (50% Salix and 50% Populus) were investigated. Total nitrogen and phosphorus content of biomass samples were measured at the beginning and end of the experiment for the leaching dynamics experiment. We found that litter mass losses (Salix, Populus and mixed leaves) were not significantly different between the two mesh size litterbags and between Lake Balaton and Kis-Balaton Wetland. Different amounts of the total nitrogen and phosphorus leaching from Salix, Populus and mixed leaves were detected. The total nitrogen contents of the plant samples were around 8-18% at the end of the investigated period. Slightly higher values were measured compared to phosphorous (27-29%).